Valuing Florida Water Resources: Water Use in Irrigated Agriculture - Tatiana Borisova; Syed Irfan Ali Shah; Tara Wade; Kelly Grogan; Xiang Bi (EDIS, 2019)
Water resources provide us with a variety of goods and services (altogether often referred to as ecosystem services or environmental services.) Part of a series entitled Economic Value of Florida Water Resources, this 5-page fact sheet written by Tatiana Borisova, Syed Irfan Ali Shah, Tara Wade, Kelly Grogan, and Xiang Bi and published by the UF/IFAS Food and Resource Economics Department assesses the economic value of the ecosystem services provided by irrigation water and shows the importance to agriculture of water resource protection and restoration. http:edis.ifas.ufl.edu/fe1057